Прогноз залежей углеводородов в Днепровско-Донецкой впадине на основе комплексной оценки космической информации ДЗЗ и наземных наблюдений - Козлов, З.В.; Лукин, А.Е.; Федоровский, А.Д. (Видавничий дім "Академперіодика" НАН України, 2007)
A method of predicting the hydrocarbon deposits on the base of the integral assessment of a remote sensing space information and ground-based observations using an algorithm and a program of multiobjective optimization by the example of Dnieper-Donets Depression territory sites is examined.